Building a Safer World: The Intersection of Agromaritime and One Health for Global Health Security to Address Emerging Challenges in the 21st century - Dicky Budiman; Sari Luthfiyah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The One Health paradigm, with its integral recognition of human, animal, and environmental health interdependencies, has garnered increasing endorsement in recent years. Equally important is the agro-maritime sector, given its crucial role in food security and international commerce, which is now acknowledged as a fundamental component within the One Health strategy. Contemporary complex health issues such as zoonotic diseases, antimicrobial resistance, and food safety threats necessitate a holistic, interdisciplinary approach that considers the trifecta of human, animal, and environmental health. The amalgamation of agro-maritime and One Health strategies is paramount in addressing burgeoning challenges that imperil global health security. These encompass the proliferation of zoonotic diseases, the surge in antimicrobial resistance, and escalating concerns surrounding food safety. The significance of advancing surveillance, monitoring, and control measures, along with fostering innovative technologies and strategies, is underscored to pre-empt and mitigate the impacts of these health threats. Spanning agriculture, aquaculture, and fisheries, the agro-maritime sector's substantial role in global health security is highlighted due to its profound influence on food production, nutrition, and environmental sustainability. The One Health model, a comprehensive approach acknowledging the intertwined nature of human, animal, and environmental health, provides a robust framework to confront emerging global health threats such as antimicrobial resistance, zoonotic disease spread, and climate change-induced health impacts. The discourse emphasizes the criticality of interdisciplinary collaboration and the deployment of a holistic perspective to tackle complex global health challenges. By strengthening the argument for the convergence of One Health and agro-maritime sectors, this paper seeks to galvanize proactive and collaborative efforts among stakeholders to fortify global health security in an increasingly unpredictable world